Awareness of drug addiction among students attending healthy life seminar - Bağcı Taylan, Şengül; Nas, İbrahim; Ediz, Çiçek (Journal of Dependence, 2019)
Objective: Addiction showed a 17-fold increase since 2009 in Turkey by reports from the United Nations. In this study, we aimed to determine the status of smoking, alcohol and other substances and to evaluate the awareness training in the seminar in addiction at Hakkari University.Method: Survey have been given to each participants. 97,4% of participants completed both the presurvey and postsurvey.Results: According to the demographic data of our survey study; smoke, alcohol and drug use rates were found to be higher and starting age was found to be lower in the males than females. Alcohol and substance use rates were found to be high in individuals with cigarette addiction. In addition, the rate of smoking was significantly higher in patients with chronic disease. The rate of those who knew the addiction treatment centers was 27.0%, this rate was observed a statistically significant increase after the seminar.Conclusion: It is clear that training in smoking, alcohol and drug addiction will increase the awareness of the individual and will lead to overcome addiction. Also; counseling, support and treatment centers should be promoted, and access to these centers should be facilitated. Thus; important steps will have been taken to prevent smoking, alcohol and drug addiction in order to protect public health.
Keywords: Drug addiction; smoking; alcohol; overcome addiction